(untitled) - Pough, F. Harvey (Upper Saddle River, N.J., 2002)
Widely praised for its comprehensive coverage and exceptionally clear writing style, this best-selling exploration of vertebrate life is the only accurate and up-to-date treatment of vertebrates that employs a phylogenetic perspective and focuses on how vertebrates work, integrating ecology, behavior, anatomy, and physiology in an evolutionary context. A new chapter on conservation draws together information about the basic biology of vertebrates and shows how it is essential for biological and regulatory decisions that affect the survival of species. Discussions of anatomy, physiology, and behavior are placed in an evolutionary context, showing readers how animals work and how they got to be the way they are. Contains information about conservation and endangered species status—related to the basic biology of the groups stresses the importance of good biological information for management and legislation. Features a Cladistic perspective which reflects the widespread adoption of phylogenetic systematics (cladistics) as the basis for determining the evolutionary relationships of organisms. Includes emphasis on conservation—Includes the application of basic biological information about organisms in programs of captive husbandry and management of threatened and endangered species. For professionals in the fields of Vertebrate Zoology, Vertebrate Biology Function, as well as Paleontology and Herpetology.
Keywords: Vertebrates, fossil,Hoá thạch động vật có xương sống